(untitled) (Applied Biological Research, 2011)
Calocybe indica, a specialty mushroom, is the third most popular mushroom in India. During present investigation 9 strains of C. indica were cultivated on wheat straw using the recommended technology. Maximum biological efficiency was obtained in strain Ci-3 (81.28%). The improvement in Ci-3, a high yielding strain, was attempted using mutagenic treatment on protoplasts. Four mutagenic treatments (one irradiation and three chemical) yielded 30 putative mutants. Growth studies of putative mutants indicated maximum growth rate of CMB-4 on wheat straw while CMN-11 gave maximum biomass on complete yeast extract medium. Mutant CMN-9 gave maximum endoglucanase (0.345 µg min-1 ml-1) and xylanase (0.54 µg min-1 ml-1) activity. Seven mutants were identified on the basis of growth and enzymes studies. Cultivation of mutants was carried out on wheat straw following hot water treatment. Four mutants (CMN-3, CMN-9, CMN-11 and CMB-4) gave significantly higher yield than the parent.